Electrospun polymeric dressings with tuned collagen type I and antimicrobial peptides activities for enhanced wound healing - Felgueiras, Helena Prado (2017)
[Excerpt] Wound dressing is an important segment of the medical and pharmaceutical market worldwide. In the past, traditional dressings were used to simply manage wounds. Nowadays, wound dressings aim faster skin regeneration, oxygen exchange and lower microbial colonization. Acute wound therapies target specific phases of wound-healing, hemostasis, inflammation, proliferation and maturation, but do not consider possible disrupts on the usual conduct of each phase [1]. Due to a number of potential stimuli, ischemia, bioburden, necrotic tissue, trauma, etc., wounds can stall in one phase of healing, typically inflammation, contributing to wound chronicity [2]. Chronic wounds are often characterized by a defective matrix and cell debris impair healing, high bacteria counts, prolonged inflammation and moisture imbalance. Conventional therapies identify and remove these barriers to wound-healing by applying individualized treatments to each barrier [3]. [...]